Accuracy of quick sequential organ failure assessment score to predict mortality in hospitalized patients with suspected infection in an HIV/AIDS reference centre in Rio de Janeiro, Brazil. (January 2019) - Moreira, J.; Paixão, A.; Oliveira, J.; Jaló, W.; Manuel, O.; Rodrigues, R.; Oliveira, A.; Tinoco, L.; Lima, J.; Grinsztejn, B.; Veloso, V.G.; Japiassú, A.M.; et al.
Abstract: Objectives: : To compare the discriminatory capacity of the quick sequential organ failure assessment (qSOFA) vs. the systemic inflammatory response syndrome (SIRS) score for predicting 30-day mortality and intensive care unit (ICU) admission in patients with suspicion of infection at an HIV reference centre. Methods: We performed a prospective cohort study including consecutive adult patients who had suspected infection and who were subsequently admitted to the medical ward. Variables related to qSOFA and SIRS were measured at admission. The performance (area under the receiver operating curve, AUROC) of qSOFA (score ≥2) and SIRS (≥2 criteria) as a predictor of 30-day mortality and ICU admission was evaluated. Results: One hundred seventy-three patients (mean ± standard deviation age, 42.6 ± 12.4 years) were included in the analysis; 107 (61.8%) were male, and 111 (64.2%) were HIV positive. Respiratory and gastrointestinal infections occurred in 49 (28.3%) and 23 (13.3%), respectively. The 30-day mortality rate was 9 (5.2%) of 173. The prognostic performance of qSOFA was similar compared to SIRS, with an AUROC of 0.68 (95% confidence interval, 0.55–0.81) and 0.69 (95% confidence interval, 0.53–0.86) (p 0.96). Twenty patients (11%) were admitted to the ICU; qSOFA and SIRS had a similar discriminatory capacity for ICU admission (AUROC 0.63 (95% confidence interval, 0.51–0.75) and 0.63 (95% confidence interval, 0.50–0.76)), respectively). Conclusions: We found a poor prognostic accuracy of the qSOFA to predict 30-day mortality in hospitalized patients suspected of infection in a setting with a high burden of HIV infection.